If interns are not employees, why demand so much? - Azrymi, Amirul Nazmi; Sahruddin, Mohammad Shafiq (Mkini Group, 2023)
This article admonishes the claims many made on the status and worth of interns in industries amidst the ongoing youth-driven campaign for interns to be compensated fairly. This article also provides counterarguments to notions that interns are not technically employees and that industries do not need interns to flourish or survive.